Teaching and learning modelling and specification based on mobile devices and cloud - Moreira, Fernando (2018)
In this paper, and in the context of a course of 1st cycle in Informatics, and following the guidelines of the Information Systems courses provided by ACM/AIS, we propose the use of Google tools and Lucidchart modeling tool, aligned with Bloom's taxonomy in our model BML Context Oriented (BML-CO) in a Requirements Engineering course based on Unified Modelling Language (UML) to modeling and specify requirements to a software system. Teaching Requirements Engineering and, in particular modeling and specification requirements, at the higher education institutions is an “arduous” task according to the literature that the proposed approach wants contribute for filling this gap.